(3habG dGJaGbjI GdLhGfH GdeJUdI HGdJLGQI ef Mbhb GdedcjI GdacQjI(B((3JQjHS(B)s - (3LdGd haGA(B, (3eMeOjfs ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2000)
(3CgejI GdMeGjI GdbGfhfjI ddedcjI GdacQjI,GdeHGOF GdCSGSjI aj GJaGbjI JQjHS,GdMeGjI GdbGfhfjI ddeHJcQGJ WHbG dGJaGbjI JQjHS,GdMeGjI GdbGfhfjI dHQGAGJ GdENJQGY,GdMeGjI GdbGfhfjI ddeHJcQGJ GdCNQi,GdMeGjI GdbGfhfjI ddYdGeGJ GdJLGQjI,GdMeGjI GdbGfhfjI ddeDTQGJ GdLZQGajIs
(3edMb U(B.50s
Keywords: (3GdYdGeGJ GdJLGQjIs; (3GdedcjI GdUfGYjIs; (3HQGAGJ GdGNJQGYs